Garden flowers - Hoare, Ben. (New York : DK, 2006)
Contains brief descriptions of different garden flowers, each with a matching sticker, and features a garden scene on which extra stickers can be arranged.
"More than 60 reusable full-color stickers"--Cover.
4.8
K-3
Keywords: Flowers -- Juvenile literature; Toy and movable books -- Specimens; Flowers; Toy and movable books; Flowers; Toy and movable books